EXAMINATION OF THE ATTITUDES OF THE STUDENTS OF THE SCHOOL OF PHYSICAL EDUCATION AND SPORTS TOWARDS THE EDUTAINMENT APPROACH - Aksakal, Nalan (International Journal of Research -GRANTHAALAYAH, 2019)
The aim of this study is to determine School of Physical Education and Sports students’ attitudes background about edutainment approach. A total of 338 students participated in the study; 118 female and 220 male. The study used Attitude Towards Edutainment Scale for data collection purposes. The data obtained were analyzed through descriptive statistics, Explanatory Factor Analysis, Correlation Analysis and Multiple Linear Regression Analysis by using SPSS 18 software. According to the findings the relationship among attitude factors regarding edutainment, correlations among factors range between ,51 and ,63. The lowest correlation value (0.51) was calculated for “perceived learning effect” and “drama” and “practice” factor while the highest correlation (0.63) for “expression and material and drama and practice” factors. Pearson correlation coefficients imply a medium level correlation among all factors. According to standardized beta (β) values in regression model, which shows the correlation among variables, “perceived learning effect” factor has the strongest effect on all recommendation and satisfaction-which are the dependent variables. In conclusion, the study found a meaningful relationship between edutainment approach and “recommendation” and edutainment approach and “satisfaction” It was also found that “satisfaction” has a strong effect on recommendation variable.